Virtual Training Session on Enhancing Data Collection and Climate Monitoring with the KMD Mobile App and Web Dashboard - Akshatha, Annaiah (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The AICCRA-KMD Mobile Application is a cutting-edge, Android-based tool developed through a collaborative effort between the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), the International Livestock Research Institute (ILRI), the Kenya Meteorological Department (KMD), and the CGIAR Initiative on Digital Innovation (CGIAR-DI). Designed as a user-friendly platform, the app serves to collect vital agro-meteorological and rainfall data directly from the field, leveraging manual rain gauges installed in farmers' fields across Kenya.